Improvement of Resveratrol Permeation through Sublingual Mucosa: Chemical Permeation Enhancers versus Spray Drying Technique to Obtain Fast-Disintegrating Sublingual Mini-Tablets - Giulia Di Prima; Giuseppe Angellotti; Amalia Giulia Scarpaci; Denise Murgia; Fabio D'agostino; Giuseppina Campisi; Viviana De Caro (MDPI AG, 2021)
Resveratrol (RSV) is a natural polyphenol with several interesting broad-spectrum pharmacological properties. However, it is characterized by poor oral bioavailability, extensive first-pass effect metabolism and low stability. Indeed, RSV could benefit from the advantage of the sublingual route of administration. In this view, RSV attitudes to crossing the porcine sublingual mucosa were evaluated and promoted both by six different chemical permeation enhancers (CPEs) as well as by preparing four innovative fast-disintegrating sublingual mini-tablets by spray drying followed by direct compression. Since RSV by itself exhibits a low permeation aptitude, this could be significantly enhanced by the use of CPEs as well as by embedding RSV in a spray-dried powder to be compressed in order to prepare fast-disintegrating mini-tablets. The most promising observed CPEs (menthol, lysine and urea) were then inserted into the most promising spray-dried excipients' compositions (RSV-B and RSV-C), thus preparing CPE-loaded mini-tablets. However, this procedure leads to unsatisfactory results which preclude the possibility of merging the two proposed approaches. Finally, the best spray-dried composition (RSV-B) was further evaluated by SEM, FTIR, XRD and disintegration as well as dissolution behavior to prove its effectiveness as a sublingual fast-disintegrating formulation.